SOME ISSUES OF THE STUDY OF THE KARAKALPAK EPOS BY THE COMPARATIVE-TYPOLOGICAL METHOD - Allambergenova, G.K. (FAN va JAMIYAT, 2016)
The article deals with the issues of comparative-typological study of the Karakalpak epos. The comparative analysis of folklore of nations with different language systems let us get acquainted closer with the best works of folklore. The comparative study of folklore of different peoples is considered to be a great contribution to the development of global literary study. The author of the article distinguishes the common and specific peculiarities of the Karakalpak epos comparing it with the epos of other peoples and using the leading experience of prominent scholars of the East and West.